The Modern Interpretation of Spiritual Education and Its Role in the Educational Process - Xatamova , Ma’rifat (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
This article presents information on the modern interpretation of spiritual education, related theories, and its role in students’ learning activities in the era of globalization